Political Parties and Women's Success in Municipal Elections in 2005 in Montérégie and Montréal (Québec, Canada). Issue 4 (2nd October 2019) - Couture Gagnon, Alexandre; Palda, Filip; Sepielak, Katarzyna
ABSTRACT: We examine the impact of political parties on the success of women and men candidates in the 2005 municipal elections of Québec's two most populous regions, Montérégie and Montréal. We built the dataset by requesting documentation from each municipality separately. This original dataset supports our two hypotheses. First, we demonstrate that the presence of political parties did not affect the difference in percentages of votes obtained by women and men candidates. No matter the gender, candidates affiliated with a political party obtained more votes than independent ones. Second, we find that gender did not affect contributions. No matter the gender, the presence of political parties and the candidates' affiliation had a positive impact on their contributions. Québec conforms to findings in the U.S. literature: women and men candidates, under similar circumstances, are equally likely to obtain votes and contributions.